Analisis Evaluasi Pelaksanaan Program Bimbingan Dan Konseling Bidang Sosial Di SMK Negeri 1 Lolowau - Arnita Niroha Halawa; Aep Saepudin; Karlis Karlis; Irnayanti Paillin; Vip Pratama (LPPM Politeknik Pratama, 2024)
Counseling guidance (BK) teachers have a very important role in developing social guidance for students at school. Their main task. includes developing abilities, overcoming social problems in the school and community environment, as well as collaborating with peers and adults. Evaluation of the implementation of social guidance and counseling programs is very important in order to assess the positive and negative impacts of relationships within and outside the school environment. The quality of evaluation of program implementation has a direct impact on the achievements of the program and its implementation. This research aims to provide an overview and objective information regarding the evaluation of the implementation of the social guidance and counseling program at SMK Negeri 1 Lolowau. The research method used was a naturalistic qualitative method with two guidance and counseling teachers as the research sample. Data collection was carried out through interviews and documentation. The results of data analysis show that the evaluation of the implementation of the social guidance and counseling program at SMK Negeri 1 Lolowau is going well. However, this research provides recommendations to counseling teachers to improve the quality of evaluation of the implementation of social guidance and counseling programs. The aim is to take a deeper look at the positive and negative impacts of social interactions, as well as to understand the achievements that have been achieved through the program.